Modelagem da precipitação com antissolvente supercrítico assistida por CFD - Cardoso, Flávia Aparecida Reitz (2014)
The use of spray drying techniques based on properties of supercritical fluids have been studied and widely reported in literature. The main advantage of the use of supercritical fluids is that they can be efficiently separated by decompression, from both organic solvents and solids, facilitating a clean recycling process of a wide variety of high quality products and the pharmaceuticaland food industry. The food solvating power of the supercritical fluid can be easily controlled by adjusting the temperature or pressure, providing new opportunities for selective crystallization, separation of impurities and control of crystal forms. From the viewpoint of thermodynamics, the techniques for particle formation using supercritical fluids more easily employed are those of the supercritical antisolvent method (SAS), as CO2 is used as the antisolvent and an organic solvent solution plus a solid solute is expanded by injection of a sub or supercritical fluid. The SAS process exploits both the high power supercritical fluid to dissolve organic solvents such as low solubility of pharmaceutical compounds in supercritical fluids, which ensures obtaining small size particles and of spherical shapes, desirable characteristics for many applications. However, this guarantee only happens if the operating conditions of the process are considered, important factors that facilitate control over the size and size distribution of particles. Given these considerations and the difficulty of finding a systemic study that relates the fluid dynamic behavior of supercritical mixture and its effects on the size, size distribution of particles in this study, a mathematical model able to predict the formation mechanisms micro, and nanoparticles chemical processes in the SAS type is proposed. The model solved numerically took into account the main physical phenomenon involved in the process, including the hydrodynamics of the jet, mass transfer, as well as the nucleation and growth kinetics of the particle, using the turbulence model of k-ε standard type solved together with mass balance, momentum and energy in two and three dimensions and merged with the population balance equations (PBE). The kinetics parameters of particles precipitation of the population balance were calculated from the experimental results of the distribution of the particles formed. The calculations of the properties including density, thermal conductivity, viscosity and mass diffusivity were determined via equation of state of Peng-Robinson with a square mixture rule of Van der Waals and Chung method Riazi and Whitson, respectively, using models for high pressure. The resolution of the model by computational fluid dynamics (CFD) allowed the discussion of the effects on the size and size distribution of particle and showed good agreement with the experimental results, allowing the approach to be applied to similar systems and helping to improve the performance of the equipment that use the SAS micronization technique, as well as allowing to predict the best operating conditions for obtaining smaller particles and spherical shapes.